Stimulation of N-methyl-D-aspartate receptors by exogenous and endogenous ligands improves outcome of brain injury. Issue 6 (December 2018) - Biegon, Anat; Liraz-Zaltsman, Sigal; Shohami, Esther
Abstract : Purpose of review: The failure of N-methyl-D-aspartate receptor (NMDAR) antagonists as a treatment for human traumatic brain injury (TBI) and stroke, along with preclinical findings of a persistent hypofunctional state of these receptors after brain injury, resulted in a new focus on NMDAR agonists, specifically those acting via the glycine site of the NMDAR. This article reviews the recent literature on positive modulators of the glycine site as a new modality for improving cognitive function in central nervous system pathology, including traumatic and ischemic brain injuries, neuroinflammation, and neuropsychiatric disorders. Recent findings: A sustained cognitive decline and NMDAR downregulation were reported in rodent models of TBI, developmental TBI, stroke, and lipopolysaccharide-induced neuroinflammation. Activation of the glycine/serine site by D-cycloserine (DCS) or D-serine ameliorated these cognitive deficits. Recent reviews and reports on the use of DCS and D-serine to modify memory function in a wide range of psychiatric conditions are generally positive. Summary: Taken together, the preclinical and clinical studies provide new, additional support for the notion that activation of the glycine/serine site should be considered a novel therapeutic approach to cognitive impairments. Specifically, as DCS is an approved drug, its translation into clinical practice should be advocated.